2019
DOI: 10.1111/hel.12663
|View full text |Cite
|
Sign up to set email alerts
|

Is Helicobacter pylori associated with Behçet's syndrome? A meta‐analysis

Abstract: Background Preceding studies have reported the relationship between Helicobacter pylori (H pylori) and Behçet's syndrome (BS), but there still exists controversy. In this study, we firstly conducted a meta‐analysis to clarify the relationship of these two diseases. Methods Articles published until July 1, 2019, in the PubMed, MEDLINE, and Embase databases with restriction of English‐language studies were searched and reviewed. According to the inclusion criteria, relevant statistical data were extracted and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Moreover, in a small cohort of patients with BD, a significant improvement in the number and size of oral and genital ulcers was observed after H pylori eradication 89 . These findings were confirmed in a recent meta‐analysis, reporting that BD patients were more susceptible to H pylori infection, with an OR of 1.39 (95% CI, 1.03‐1.87) 90 …”
Section: Immune‐mediated Diseasesmentioning
confidence: 61%
See 1 more Smart Citation
“…Moreover, in a small cohort of patients with BD, a significant improvement in the number and size of oral and genital ulcers was observed after H pylori eradication 89 . These findings were confirmed in a recent meta‐analysis, reporting that BD patients were more susceptible to H pylori infection, with an OR of 1.39 (95% CI, 1.03‐1.87) 90 …”
Section: Immune‐mediated Diseasesmentioning
confidence: 61%
“…89 These findings were confirmed in a recent meta-analysis, reporting that BD patients were more susceptible to H pylori infection, with an OR of 1.39 (95% CI, 1.03-1.87). 90…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…There was also a strong correlation between H. pylori infection and halitosis, but the mechanism was not clear as it was difficult to determine whether the halitosis was induced by H. pylori in the stomach or caused by the changes of oral microflora induced by H. pylori infection ( Anbari et al., 2019 ). A study analyzed the correlation between Behçet’s syndrome (BS) and H. pylori infection and found that BS patients had a higher rate of H. pylori infection, and the clinical symptoms including oral ulceration, genital ulceration, and cutaneous lesions could be improved after H. pylori eradication ( Yu et al., 2019 ). However, its specific mechanism remains to be explored.…”
Section: Helicobacter Pylori and Oral Microbiomementioning
confidence: 99%
“…Several investigations have tried to identify key pathogenetic mechanisms suggesting the microorganism as a systemic pathogen [14]. Specifically, the remodeling of the host's immune response, enabling H. pylori to escape early clearance and promoting its survival in the host environment, may enhance, as a side effect, the risk of developing organ-specific autoimmune manifestations such as Behçet disease [15], type-1 diabetes mellitus [16], rheumatic disorders [17], and systemic lupus erythematosus [18], to mention a few [19]. In particular, H. pylori has been implicated in autoimmune thyroid disorders (AITDs) [20] as well as in a number of non-autoimmune TDs.…”
Section: Introductionmentioning
confidence: 99%